Inhibition of Receptor Interacting Protein Kinases Attenuates Cardiomyocyte Hypertrophy Induced by Palmitic Acid. (4th January 2016) - Zhao, Mingyue; Lu, Lihui; Lei, Song; Chai, Hua; Wu, Siyuan; Tang, Xiaoju; Bao, Qinxue; Chen, Li; Wu, Wenchao; Liu, Xiaojing
Abstract : Palmitic acid (PA) is known to cause cardiomyocyte dysfunction. Cardiac hypertrophy is one of the important pathological features of PA-induced lipotoxicity, but the mechanism by which PA induces cardiomyocyte hypertrophy is still unclear. Therefore, our study was to test whether necroptosis, a receptor interacting protein kinase 1 and 3 (RIPK1 and RIPK3-) dependent programmed necrosis, was involved in the PA-induced cardiomyocyte hypertrophy. We used the PA-treated primary neonatal rat cardiac myocytes (NCMs) or H9c2 cells to study lipotoxicity. Our results demonstrated that cardiomyocyte hypertrophy was induced by PA treatment, determined by upregulation of hypertrophic marker genes and cell surface area enlargement. Upon PA treatment, the expression of RIPK1 and RIPK3 was increased. Pretreatment with the RIPK1 inhibitor necrostatin-1 (Nec-1), the PA-induced cardiomyocyte hypertrophy, was attenuated. Knockdown of RIPK1 or RIPK3 by siRNA suppressed the PA-induced myocardial hypertrophy. Moreover, a crosstalk between necroptosis and endoplasmic reticulum (ER) stress was observed in PA-treated cardiomyocytes. Inhibition of RIPK1 with Nec-1, phosphorylation level of AKT (Ser473), and mTOR (Ser2481) was significantly reduced in PA-treated cardiomyocytes. In conclusion, RIPKs-dependent necroptosis might be crucial in PA-induced myocardial hypertrophy. Activation of mTOR may mediate the effect of necroptosis in cardiomyocyte hypertrophy induced by PA.